Energy use flows in the supply chains of the world economy: A full account of both primary and intermediate inputs. (20th October 2021) - Wu, Xudong; Guo, Jinlan; Chen, Guoqian; Wu, Xiaofang; Meng, Jing; Alhodaly, Mohammed; Wakeel, Muhammad
Abstract: As an extension of our previous work (Wu et al., 2019b), this study uses a positive accounting manner to track the circulation of energy use via interregional trade, by taking a full account of indirect energy usage related with primary inputs as well as intermediate inputs. The aggregate amount of interregional shift of energy use is about six times larger than that recorded in the preceding work, revealing the robust flows of energy use associated with intermediate products traded across global supply chains. The United States is a crucial sink of energy use in the world, serving the leading net importer of energy use in final trade and the second biggest net importer in intermediate trade. Around 60% of the energy use initiated by its final consumption stems from other regions. For Mainland China as the third largest net importer of energy use in intermediate trade and the leading net exporter in final trade, around 60% of local primary energy exploitation sinks into final consumption abroad. For sustainable economic growth and efficient energy management, countries are recommended to be further integrated in the international supply chains by accurately pinpointing their roles in the trading market of energy use.